2009
DOI: 10.2353/ajpath.2009.090091
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of Stk39 in B-Cell Lymphoma Inhibits Apoptosis from Genotoxic Stress

Abstract: Leukemias and lymphomas arise by genetic and epigenetic alterations of previously healthy lymphocytes. B-cell lymphoma is the most frequent lymphocyte malignancy, with certain tumor subtypes characterized by recurring genetic alterations that include reciprocal chromosome translocations between IG loci and CCND1, BCL2, MYC, and BCL6.1 These rearrangements place tumor-promoting genes under the control of IG rather than endogenous regulatory elements, leading to their dysregulated expression. Epigenetic changes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…It is possible that SPAK may be involved in these actions in cell division that result in the slowed cell proliferation observed in WNK1 and SPAK knockdown HUVECs. This may also be related to the earlier finding that SPAK induces apoptosis in a caspase-dependent manner in response to genotoxic stress (62). Modulating SPAK activity directly or indirectly via WNK1 knockdown could lead to proliferation defects mediated by deregulation of cellular responses to DNA damage or other stress-induced apoptotic mechanisms.…”
Section: Discussionsupporting
confidence: 53%
“…It is possible that SPAK may be involved in these actions in cell division that result in the slowed cell proliferation observed in WNK1 and SPAK knockdown HUVECs. This may also be related to the earlier finding that SPAK induces apoptosis in a caspase-dependent manner in response to genotoxic stress (62). Modulating SPAK activity directly or indirectly via WNK1 knockdown could lead to proliferation defects mediated by deregulation of cellular responses to DNA damage or other stress-induced apoptotic mechanisms.…”
Section: Discussionsupporting
confidence: 53%
“…Polymorphisms in this gene have been linked to risk of hypertension (33-35). Epigenetic silencing of STK39 through DNA hypermethylation in B-cell lymphoma appears to promote cancer progression by inhibiting apoptosis in cells with DNA damage (36). …”
Section: Discussionmentioning
confidence: 99%
“…In 2009, hyper-methylation and repressed SPAK expression levels were found in B cell lymphomas. It was also shown that caspase-dependent apoptosis was impaired when SPAK expression was genetically knocked down, indicating that the loss of SPAK might promote increased cell survival and increased resistance to cancer (14). …”
Section: Physiological Roles Of Spak and Osr1 In Mammalian Systemsmentioning
confidence: 99%